Sistem Infomasi Geografis Pemetaan Penyebaran Penyakit ISPA, Hipertensi, dan Asma Berbasis Web Di Kabupaten Bondowoso - Nanja Auliya Syafina; Safira Nur Fauziyah; Dina Ayu Mashita; Niyalatul Muna; Mochammad Choirur Roziqin (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Unfavorable environmental conditions, economic factors and public health behavior are still bad, causing the number of cases of morbidity caused by tropical diseases is still high. Health agency programs in preventing and eradicating disease will be very effective when receiving support from an information system to review the spread of disease. Referring from 2015 East Java Health Profile, the highest AKI in 2015 was in Bondowoso with 188 per 100,000 live births or as many as 19 people. The types of diseases with the highest number of patients were acute upper respiratory tract infections reaching 31,457 patients. The Geographical Information System for Mapping the Spread of ISPA, Asthma and Hypertension in Bondowoso Regency was prepared using the Google Fusion Table (GFT). This system can be accessed quickly, easily, requires an internet network and can provide information on mapping the spread of ISPA, asthma and hypertension in the Bondowoso area. The map on the system is able to display information including sub-district names, number of cases, number of cases ISPA, Asthma, and Hypertension specifically year 2012 and 2013. This system uses polygon features to mark sub-districts with different colors according to the number of cases. The system also provides a menu to change data for admins who have access rights. Keywords— Asthma, GFT, Hypertension, ISPA, Mapping.